Keris Sebagai Salah Satu Kebudayaan Materi - Priyanto Priyanto (Program Pendidikan Vokasi Universitas Indonesia, 2013)
ABSTRACT. “Keris” is one of the material culture as collection museum can be assumed as souvenir, fetish,and collection. The Museum should be giving about the meaning of “keris” and its community. Museum notonly show subject as material cultural but also show other aspect as social, religious an aspect dayly acktivity ofits community.Keywords: “keris”,material culture, museum